Teaching Digital ESL Communication Skills for Remote Work Environments - Dziubata, Zoriana (Pedagogical Discourse, 2025)
The research is aimed at investigating the need to specifically address the application of English language skills and using AI tools within remote professional communication contexts due to the growing shift towards remote and AI-enhanced work environments. The term “digital ESL communication skills” has been defined as follows: the application of English language skills for professional, task-based interaction in digital environments, including written and spoken communication through emailing, instant messaging, video conferencing, project management platforms and AI chatbots. Having applied such methods as literature review, a stakeholders’ survey of 116 students and professionals, document analysis and the analysis of leading Business English course syllabi, it has been demonstrated that there is a gap in current ESL education and the need to integrate English language learning with practical tasks that are required for asynchronous professional communication, video conferencing and intelligent use of AI tools in remote digital work environments. 7 core skill areas such as: slack-style messaging, digital professional writing, task management communication, video conferencing, AI tool usage, digital etiquette and soft skills development for professional success in remote settings, have been identified and described according to current real-world professional tasks within a remote, tech-integrated context (needs analysis). Recommendations on teaching digital English communication and AI literacy have been provided on each skill area. These included the lists of targeted vocabulary and grammar as well as recommended activities and resources aimed at contributing to the methodological aspect of teaching digital ESL communication skills. The research is a step towards modernizing ESL courses at college and university level for today’s remote or hybrid globalized, tech-driven workplace.